DEVELOPMENT OF VACCINES BASED ON ADENOVIRAL VECTORS: A REVIEW OF FOREIGN CLINICAL STUDIES (PART 1) - L. V. Cherenova (SPb RAACI, 2017)
There are no effective approaches to treatment and prevention of many infectious diseases representing a significant danger to humans. So far, mass vaccine immunization is among the most efficient and widely used approaches to prevent outbreaks of viral and bacterial infections. Mass immunization helps to reduce the number of carriers of infections, thus significantly decreasing probability of infection dissemination. Recent promising developments include genetically engineered vaccines based on adenoviral vectors, many of which are already at various stages of clinical trials. Genetic immunization with recombinant adenovirus-based vaccines allows delivery of the genes encoding only required antigens to human cells, thus allowing avoidance of conventional vaccines, e.g., live pathogenic viruses and bacteria, and providing versatile technologies for vaccine development. These advances significantly reduce the time needed for vaccine production and, respectively, the development and creation of new vaccines, thus being an important factor in decreasing risk of epidemics and pandemics. Advantages of adenoviral vectors include high ability of penetration into human cells, a potential for induction of both humoral and cellular immune response, rather long and active production of antigens following administration of adenoviral vectors into the human, safe usage, ease of obtaining preparative quantities of vaccines. In this review, we provide information about the ongoing worldwide clinical trials of adenoviral vector-based vaccines against various infectious diseases, like as to consider selection parameters of volunteers participating in the testing, vaccination schedule, doses and methods of drug administration, results of completed experiments, and preliminary data on currently ongoing research.